DEVELOPMENT AND PROSPECTS OF AUTOMOBILE TRANSPORT IN UZBEKISTAN. (Multidisciplinary Journal of Science and Technology, 2024)
The development of the automobile transport system in Uzbekistan has undergone significant changes in recent years, driven by urbanization, economic growth, and the need for improved infrastructure. This progress has led to the modernization of road networks, expansion of public transport systems, and an increase in the number of vehicles. However, the sector faces challenges such as traffic congestion, environmental concerns, and the need for sustainable development. This study explores the current state of automobile transport in Uzbekistan, examining its development trends, challenges, and future prospects. It also highlights the importance of enhancing infrastructure, adopting green technologies, and improving traffic management to ensure the sector’s continued growth. The future of automobile transport in Uzbekistan depends on balancing economic growth with environmental sustainability, aiming to provide a modern, efficient, and eco-friendly transport system for the population.